Brinquedos e brincadeiras na pré-escola : um estudo das imagens lúdicas nos tempos e espaços do brincar - Rodrigues, Josiane (2019)
The presented thesis is the result of a study with a group of children, it was carried out in the doctorate course in Education and brings some aspects of the socioanthropology field of study. The research named ―Preschool toys and games - a study of the ludic images in times and spaces for playing‖ had as main objective knowing what ludic implications arise when pre-school children are interacting with toys and games in times and spaces for playing. From this perspective, the problem concerns if whether the pre-school stage goes beyond the function of caring and educating and and if it uses toys and games as a support for the construction of the children's Ludic Culture. The specific objectives were: to perceive if times and spaces of toys and games are used to learn and / or entertain; identify the teacher and institution‘s pedagogical / didactic / educational intention when the children are playing with their toys (real or not) and to identify the ludic images produced within the playing process. The methodological choose is by the qualitative approach of ethnographic type, in a descriptive and interpretative study. The researcher herself, using description and induction to apprehend the phenomena, was the main instrument in the data gathering and analysis process, which also uses a field notebook that contains the daily notes, besides the film and áudio recordings and, mainly, photographic recordings. The data were presented in three ways: in the routine, with the ludic images and in the list of moments, activities and spaces. The images obtained were analyzed in talks with the authors, with the scenes produced (results of the audios and videos) and with the records of the field notebook. The results pointed out that the images brought out the ludic way which the group behaves in time and space, making playing their greatest occupation. Playing is not only a part of child‘s life, but it is the child's life itself.